Awareness and knowledge of cyber ethics by library and information science doctoral students in two Nigerian universities. (2017) - Adetimirin, Airen
Library and information science (LIS) doctoral students need to source for information from various information sources and this necessitate the use of information and communication technology (ICT) for their research and other academic activities. Their behaviour when using ICT will be determined by their awareness and knowledge of the legal, moral and social issues. This study, therefore, investigated the current level of awareness and knowledge that LIS doctoral students have about cyber ethics. The privacy, accuracy, property and accessibility (PAPA) framework is the anchor for this study. A survey design and a questionnaire were adopted to collect data from doctoral students in two Nigerian universities. Data collected was analysed using descriptive statistics and cross tabulation. Findings revealed that the level of awareness and knowledge of cyber ethics by the students were high (> 83.4%) and (> 73.5%) respectively, although Ilorin showed a higher level of awareness and knowledge than Ibadan. The adherence to PAPA framework was in the range of 51.8%-92.0%. LIS doctoral students are highly aware and knowledgeable about cyber ethics. Cyber ethics education should be provided to promote compliance with cyber ethics among the LIS doctoral students in Nigerian universities.